Persepsi Petani terhadap Pilihan Menjual Padi Kepada Penebas atau Perpadi (Kasus Subak Benel, Desa Kaliakah, Kecamatan Negara, Kabupaten Jembrana) - WIRAWAN, I MADE PRASADA ARY; SUARDI, I DEWA PUTU OKA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Farmers Perception Of Options To Sell Rice Penebas Or Perpadi (especially in Subak Benel, Kaliakah Village, Negara districts, Jembrana Regency) Various efforts have been implemented by the Provincial Food Crops Agency of Bali to stabilize the price of grain, this is done by giving Funds of Rural Economic Empowerment Capital to the government for the purchase of rice. Although it has been done from 2003, farmers are still selling it to Penebas with a bondage system. The purpose of this study to determine the perception of farmers to the choice of selling rice to Perpadi or Penebas seen and differences in farmers' perceptions of the choice of selling rice to Penebas or Perpadi. The research location is located in Subak Benel, Kaliakah Village, State District, Jembrana District. The analytical method used is qualitative descriptive that aided with score, to answer the purpose of research by using questionnaire. The results of this study indicate that the perception of farmers to the choice of selling rice to Perpadi better than to Penebas. This is seen in the achievement of the farmers' choice of selling paddy to Perpadi is very good and to Penebas is good. The difference of Perpadi with Penebas is measured through Different Test with SPSS Independent Sample T test program which the result of Sig value. Or p value of 0.004 where <0.05 then there is a statistically significant difference in probability 0.05, the mean difference or mean of both groups is shown in Mean Difference ie .29559.